Radical management of solid ameloblastoma of the mandible: Report of a case with 5-year follow-up - Jorge-Boos, F. B.D. [UNESP]; Hochuli-Vieira, E. [UNESP]; Stabile, G. A.V.; Sonoda, C. K. [UNESP]; Souza, F. A. [UNESP]; De Melo, W. M. [UNESP] (My University, 2014)
Introduction: Ameloblastoma is a true neoplasm of odontogenic epithelial origin. This pathology can be classified into 4 groups: unicystic, solid or multicystic, peripheral, and malignant. Solid ameloblastomas of the mandible are the most common of them, and represent a challenging group of tumours to treat; in addition the follicular histopathological subtype has a high likelihood of recurrence. Thus, the challenges in the management of this tumour are to provide complete excision in addition to reconstruct the bony defect, in order to provide the patient with reasonable cosmetic and functional outcome. With this in mind, this paper aimed to describe the management of a solid multilocular ameloblastoma of follicular subtype in a 39-year-old female. Case report: The authors report a case of a solid multilocular ameloblastoma of follicular subtype in a 39-year-old female who was successfully treated by partial resection of the mandible with immediate reconstruction using an iliac crest, as a donor site. After 15 months, the patient was rehabilitated using titanium implant dentistry, and has been followed up for 5 years without signs or symptoms of recurrence. Conclusion: Correct surgical planning is the key for successful management of solid ameloblastoma with multilocular features, which is best treated using radical resection with immediate reconstruction, which ensures complete tumour excision, prevents recurrence, and enables fast and safe dental rehabilitation. Biomedical prototypes should be used since they provide acceptable precision and are useful for surgical planning.